2007
DOI: 10.1172/jci30562
|View full text |Cite
|
Sign up to set email alerts
|

The role of CXC chemokines in pulmonary fibrosis

Abstract: The CXC chemokine family is a pleiotropic family of cytokines that are involved in promoting the trafficking of various leukocytes, in regulating angiogenesis and vascular remodeling, and in promoting the mobilization and trafficking of mesenchymal progenitor cells such as fibrocytes. These functions of CXC chemokines are important in the pathogenesis of pulmonary fibrosis and other fibroproliferative disorders. In this Review, we discuss the biology of CXC chemokine family members, specifically as it relates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
209
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(223 citation statements)
references
References 106 publications
(152 reference statements)
8
209
0
6
Order By: Relevance
“…5 To dissect the mechanism of fibrocyte trafficking in response to liver injury, a CCR1 (or CCR2) receptor knockout mouse was crossed with a Col-Luc mouse and used for BM transplantation into lethally irradiated wild-type mice ( Figure 3D) 18 and undergo several stages of maturation. 19 Meanwhile, the BM counterpart of tissue fibrocytes has not been identified.…”
Section: Ccr2 and Ccr1 Regulate Fibrocyte Migration In Response To CCmentioning
confidence: 99%
See 1 more Smart Citation
“…5 To dissect the mechanism of fibrocyte trafficking in response to liver injury, a CCR1 (or CCR2) receptor knockout mouse was crossed with a Col-Luc mouse and used for BM transplantation into lethally irradiated wild-type mice ( Figure 3D) 18 and undergo several stages of maturation. 19 Meanwhile, the BM counterpart of tissue fibrocytes has not been identified.…”
Section: Ccr2 and Ccr1 Regulate Fibrocyte Migration In Response To CCmentioning
confidence: 99%
“…4 Fibrocytes contribute to fibrogenesis of skin, lungs, kidneys, and liver. 5 It has been demonstrated that CD45 ϩ and collagen ␣1(I) ϩ fibrocytes migrate to the injured liver in response to cholestasis 4 and comprise approximately 3% to 5% of the cells producing collagen type I. Despite low numbers, inhibition of fibrocyte recruitment via administration of human serum amyloid protein, 6 a natural inhibitor of fibrocyte migration and differentiation, effectively attenuated fibrosis in lungs, 7 kidneys, 8 and liver (our unpublished observation), emphasizing an important role for fibrocytes in fibrogenesis of parenchymal organs.…”
mentioning
confidence: 99%
“…8,9,[12][13][14] Part of such host immune responses involves the production of antiviral and inflammatory cytokines and chemokines from infected airway epithelial cells and leukocytes, including interferon (IFN)-␣/␤, TNF-␣, IFN-␥, keratinocytederived chemokine (KC), monocyte chemoattractant protein-1 (MCP-1), macrophage inflammatory protein-1 (MIP-1)␣/␤, MIP-3␣, interferon-␥ inducible protein 10 (IP-10), and regulated on activation normal T-cell expressed and secreted (RANTES). 9,[15][16][17] Cytotoxic CD8 T cells play an important role in influenza viral clearance by lysing virus-infected cells, and effective viral clearance from the lung is usually achieved within 7 to 10 days after primary infection. 8,12,13 A strong CD4 T-helper response is believed to contribute to the generation of robust hu-moral responses, important for neutralization of the virus.…”
mentioning
confidence: 99%
“…Angiogenesis is a complex process regulated by numerous proangiogenic and angiostatic forces (25). Our laboratory has begun to determine the proangiogenic growth factors that may contribute to neovascularization in animal models of left pulmonary artery obstruction (24).…”
mentioning
confidence: 99%